2023
DOI: 10.15586/aei.v51i1.776
|View full text |Cite
|
Sign up to set email alerts
|

Chryseriol attenuates the progression of OVA-induced asthma in mice through NF-κκB/HIF-1αα and MAPK/STAT1 pathways

Abstract: Background: Asthma is a hackneyed chronic inflammatory disease of the airway. Chryseriol (CSR) is a kind of flavonoid, and has the effect of bronchiectasis, indicating its potential application for treating respiratory diseases. However, the functions of CSR in asthma have not been reported till now. Materials and methods: The histopathologic changes of the lung tissues were assessed by hematoxylin and eosin staining. The cell apoptosis was identified through terminal deoxynucleotidyl transferase-mediated dUTP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…In our research on mice with an induced asthma model using OVA administration, we observed severe pathological changes, including lung histological alterations, enriched BALF proteins, increased wet/dry ratio of lung tissues, and impaired lung function. These findings were consistent with previous studies [ 26 , 27 ]. However, after administering Arctiin, the pathological changes were markedly alleviated.…”
Section: Discussionsupporting
confidence: 94%
“…In our research on mice with an induced asthma model using OVA administration, we observed severe pathological changes, including lung histological alterations, enriched BALF proteins, increased wet/dry ratio of lung tissues, and impaired lung function. These findings were consistent with previous studies [ 26 , 27 ]. However, after administering Arctiin, the pathological changes were markedly alleviated.…”
Section: Discussionsupporting
confidence: 94%
“…The sensitizing doses utilized in current murine studies typically range from 10 to 100 μg 7,17–19 . However, the effects of various doses within this range have not been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitizing doses utilized in current murine studies typically range from 10 to 100 μg. 7 , 17 , 18 , 19 However, the effects of various doses within this range have not been thoroughly investigated. In 1999, Sakai et al 20 demonstrated the impact of sensitive OVA doses (0, 10, 100, and 1000 μg) on AHR; their study suggested that sensitization with a dose of 10 μg may be more effective than with a dose of 100 μg but almost completely inhibited at a dose of 1000 μg.…”
Section: Discussionmentioning
confidence: 99%
“…[9] Simultaneously, chrysoeriol can slow down the progression of OVA-induced asthma in mice by inhibiting NF-κB/ HIF-1α and MAPK/STAT1 pathways, which is consistent with the GO enrichment results. [10] In the present research, the KEGG database was employed for pathway enrichment analysis. It was observed that within the simulated pathway, VEGFA and HIF-1α serve as crucial nodes in combating TNBC cell pathways.…”
Section: Discussionmentioning
confidence: 99%